Dietary magnesium intake, serum high sensitivity C-reactive protein and the risk of incident knee osteoarthritis leading to hospitalization—A cohort study of 4,953 Finns - Konstari, Sanna (PLoS One, 2019)
OBJECTIVES: To study whether low dietary magnesium (Mg) intake and serum high sensitivity C-reactive protein (hs-CRP) predict the development of clinical knee osteoarthritis (OA). METHODS: The cohort consisted of 4,953 participants of a national health examination survey who were free of knee and hip OA at baseline. Information on the incidence of knee OA leading to hospitalization was drawn from the National Care Register for Health Care. During the follow-up of 10 years, 123 participants developed incident knee OA. Dietary magnesium intake was assessed on the basis of a food frequency questionnaire from the preceding year. We used Cox’s proportional hazards model to estimate the strength of the association between the tertiles of dietary Mg intake and incident knee OA, adjusted for baseline age, gender, energy intake, BMI, history of physical workload, leisure time physical activity, injuries, knee complaints, the use of Mg supplements, and serum hs-CRP levels. RESULTS: At baseline, dietary Mg intake was inversely associated with serum hs-CRP even after adjustment for all the potential confounding factors. During the follow-up, the adjusted hazard ratios (with their 95% confidence intervals) for incident knee OA in dietary Mg intake tertiles were 1.00, 1.28 (0.78–2.10), and 1.38 (0.73–2.62); the p value for trend was 0.31. Serum hs-CRP level at baseline did not predict incident knee OA. CONCLUSIONS: The results do not support the hypothesis that low dietary Mg intake contributes to the development of clinical knee OA, although Mg intake is inversely associated with serum hs-CRP level.